2019
DOI: 10.1002/app.48678
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic PLGA‐PEG‐PLGA triblock copolymer nanogels varying in gelation temperature and modulus for the extended and controlled release of hyaluronic acid

Abstract: Different compositional parameters of poly(D,L‐lactic‐co‐glycolic acid)‐b‐poly(ethylene glycol) triblock copolymers (PLGA‐PEG) were varied to analyze their effect on gel formation and mechanical properties. Parameters such as hydrophilic/hydrophobic ratio (PLGA/PEG ratio), lactic acid/glycolic acid ratio (LA/GA ratio), PEG molecular weight (PEG Mw), polymer solution concentration, copolymer molecular weight (Mw), and polydispersity index (PDI) were studied in this work. For copolymers with PEG Mw of 1500 Da, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 76 publications
(164 reference statements)
0
24
0
Order By: Relevance
“…They have also claimed that an extended and controlled release of HA, beyond 2 weeks could be built from injectable hydrogels modified with a noncovalent interacting agent, poly(l-lysine) or PLL. Smaller PLL chains slowed down the HA release kinetics, while larger PLL chains produced a release profile similar to the unmodified hydrogels [50].…”
Section: Controlled Release Of Ha From Other Biomaterialsmentioning
confidence: 89%
See 1 more Smart Citation
“…They have also claimed that an extended and controlled release of HA, beyond 2 weeks could be built from injectable hydrogels modified with a noncovalent interacting agent, poly(l-lysine) or PLL. Smaller PLL chains slowed down the HA release kinetics, while larger PLL chains produced a release profile similar to the unmodified hydrogels [50].…”
Section: Controlled Release Of Ha From Other Biomaterialsmentioning
confidence: 89%
“…Osorno et al [50] produced poly(d,l-lactic-co-glycolic acid)-b-poly(ethylene glycol) triblock copolymers (PLGA-PEG) matrices to encapsulate HA and studied its controlled release. They focused on copolymer gel formation and mechanical properties on release kinetics of HA.…”
Section: Controlled Release Of Ha From Other Biomaterialsmentioning
confidence: 99%
“…These gels can be used in combination with other natural and synthetic polymers to design more efficient matrices for the extended and controlled release of drugs. 9 Different drugs and targeting moieties can be incorporated into the system, allowing for the design of more specific and effective drug release platforms. For instance, these injectable systems can be used for a variety of ocular applications, including but not limited to, macular degeneration and secondary cataracts or posterior capsule opacification (PCO).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we recently demonstrated that PLL can slow down the release rate and extend the release time of hyaluronic acid from these hydrophobic platforms. 9,13,14 Other localized medical conditions that can be treated by using these novel platforms are postsurgery pain, bone regeneration, spinal cord injury repair, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation